Experimental observation of Jute/Epoxy composite plate subjected to impact loading - Omar, Nurihan; Syed Mohd, Sharifah Najwa; Aminanda, Yulfian; Syed Mohamed Ali, Jaffar; Kashif, Syed Muhammad (2011)
World is currently focusing on alternate material sources that are environment friendly and biodegradable in nature. Due to the increasing environmental concerns, biocomposite made from natural fibers and polymeric resin, is one of the recent developments in the industry and constitute the present scope of experimental work. This work presents elaborate explanation on advantages, mechanical and physical behavior of jute fiber–epoxy composites, one of the renewable alternatives. The bicomposite is experimentally investigated in case of low velocity impact loading. The experimental observations in term of damage mechanism, maximum force and maximum energy absorption are studied to understand the effect of fiber orientation. A comparative study with typical synthetic fibers like carbon or glass is also conducted. The characterization tests on jute-epoxy show that the tensile behavior is non linear as found for carbonepoxy or glass-epoxy plate.